Impact of COVID-19 and associated lockdown on livestock and poultry sectors in India - Biswal, Jyotsnarani; Kennady, Vijayalakshmy; Rahman, Habibar (Veterinary World, 2020)
The COVID-19 pandemic and the associated lockdown for a long period have created a significant adverse impact on different sectors, including that of the agriculture and other allied sub-sectors in India and several other countries. The present review aimed to depict the impact of this pandemic and the lockdown on the livestock and poultry sectors in the country, which has been one of the fastest-growing sectors in recent years. Inadequacy of country-wide information has been a major bottleneck for having a thorough understanding of the impact of the prolonged lockdown on different sub-sectors of livestock and poultry. In the present case, an in-depth analysis of the subject has been made through the collation of available published materials and information collected through public contacts. The pandemic and the associated lockdown has not only caused enormous distress to the millions of poor and marginal farmers for saving their crops and/or livestock and thereby assuring their livelihoods but also impacted the overall poultry, dairy, and other livestock production systems and associated value chains, nutrition and health care, and labor availability. The paper highlights various dimensions of the impacts, namely, reduction in demand of different commodities, wastage of the produce due to the closure of transport and market chains, distress sale of the produce, and labor shortage and revival strategies taken by the government and associated enterprises. The present impact study although gives a picture about the overall present scenario, a systematic study through the collection of primary data from all over the country is suggested, which will provide a holistic view of the impact on each of the sub-sectors and the associated value chains.